An analysis of energy use, energy intensity and emissions at the industrial sector of Malaysia - Abdul Hakim, Saidur Rahman; Md., Hasanuzzaman; Abdul Sattar, M.; Hassan, Masjuki; Magami, Irfan Anjum; Mohiuddin, A. K. M. (Universiti Malaya, 2007)
Malaysia is a developing country which has transformed itself from more on producer of raw materials to an emerging multisector economy in a span of 40 years. Growth was almost exclusively driven by exports - particularly of electronics. This paper presents the energy consumption trend in Malaysian industrial sector. Malaysian Industrial Development Authority (MIDA) conducts survey to get raw data of energy (Fuel oil, diesel, petrol, kerosene, gas and electricity) consumption behavior for each year. The raw data has been processed by the data processors to analyze the actual behavior of energy consumption in different sub-sectors over that period. Energy intensity which is the key indicator of energy performance of a country and emissions has been calculated. The study was carried out for 2 years in 1988 and 1998. It was found that during the year 1988 and 1998, fuel oil is used more than other fuels. The energy intensity of the nonmetallic section was higher both in the years 1988 and 1998. In the year 1998, the energy intensity of chemical industries was lower. Where as, the energy intensity of wood and chemical industries were low in the year of 1988. The emissions of the food sector are higher both in the year 1988 and 1998. The emissions of the entire sector are more in the year of 1998 compare to the year of 1988. The analysis shows that over all emission is 5 times in the year of 1998 compare to that of 1988.